Consistency and Inconsistency in Caregiver Reporting of Vocabulary. Issue 1 (2nd January 2022) - Arunachalam, Sudha; Avtushka, Valeryia; Luyster, Rhiannon J.; Guthrie, Whitney
ABSTRACT: Vocabulary checklists completed by caregivers are a common way of measuring children's vocabulary knowledge. We provide evidence from checklist data from 31 children with and without autism spectrum disorder. When asked to report twice about whether or not their child produces a particular word, caregivers are largely consistent in their responses, but where they are inconsistent, these inconsistencies affect verbs more than nouns. This difference holds both for caregivers of children with autism spectrum disorder and caregivers of typically-developing children. We suggest that caregivers may be less sure of their child's knowledge about verbs than nouns. This data converges with prior evidence comparing language samples of words children produce in a recorded interaction with checklist data, and it has implications for how researchers use checklist data in cases where the reliability of estimates of verb knowledge is critical.